2018
DOI: 10.4149/gpb_2017029
|View full text |Cite
|
Sign up to set email alerts
|

Novel neuroprotective role of hydrogen sulfide in a rat model of stress brain injury

Abstract: Hydrogen sulfide (H2S) is a gaseous mediator recognized as important neuromodulator agent in the central nervous system. Since stress is among the most important factors involved in several pathophysiological brain processes. This study aim to investigate the effect of exogenous H2S on the possible negative effect of stress on the brain of rats and the underlying mechanisms. Rats were divided into 3 groups: control, stressed, H2S treated + stress. Brain injury markers measured were serum S100 protein and gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…The significant increase in iNOS levels with XE exposure observed in the current study can be explained by the significant increase of iNOS level that in turn increased NO production in rats exposed to XE in comparison with control and NaHS groups and this result is in agreement with previous studies (Saber et al, 2019). The overexpression of NO with stress results in formation of reactive nitrogen species that is considered to be one of the leading causes of injury with stress exposure (Elbassuoni and Nazmy, 2018) and as found in the present study.…”
Section: -Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The significant increase in iNOS levels with XE exposure observed in the current study can be explained by the significant increase of iNOS level that in turn increased NO production in rats exposed to XE in comparison with control and NaHS groups and this result is in agreement with previous studies (Saber et al, 2019). The overexpression of NO with stress results in formation of reactive nitrogen species that is considered to be one of the leading causes of injury with stress exposure (Elbassuoni and Nazmy, 2018) and as found in the present study.…”
Section: -Discussionsupporting
confidence: 92%
“…H2S can limit ROS either by directly scavenging free radicals, thus regulating oxidative signaling pathways, or by suppressing the inflammatory response (Stein and Bailey, 2013). The inducible nitric oxide synthase (iNOS) is scarcely present normally but can be expressed during immunological challenge and stress (Elbassuoni and Nazmy, 2018). The significant increase in iNOS levels with XE exposure observed in the current study can be explained by the significant increase of iNOS level that in turn increased NO production in rats exposed to XE in comparison with control and NaHS groups and this result is in agreement with previous studies (Saber et al, 2019).…”
Section: -Discussionmentioning
confidence: 99%
“…Hydrogen sulfide (H 2 S), the third gasotransmitter after carbon monoxide (CO) and nitric oxide (NO) (Wang, 2010), exerts protective effect in the CNS (Zhang and Bian, 2014;Panthi et al, 2016;Elbassuoni and Nazmy, 2018). Emerging evidence has indicated that H 2 S has anti-oxidative, anti-ER stress, and antiapoptotic properties in the CNS (Jiang et al, 2011;Nie et al, 2013;Li et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%
“…Newborns diagnosed with asphyxia at birth and followed up to 2 years of age, saw that lesions in neuronal structures generated in the prenatal period, are possible to be identified right at birth, within 24 h postnatal [49]. Additionally, a study that evaluated the effect of hydrogen sulfide in a model of brain injury by stress in rats, identified an increase in serum NSE levels, as well as an increase in the levels of ROS and reactive nitrogen species (RNS), causing oxidative stress [51]. In the maternal exposure to infections or inflammations in the prenatal period, an increase in NSE in the offspring was found previously.…”
Section: Discussionmentioning
confidence: 99%